Dark matter signals on laser interferometer. (February 2020) - Tsuchida, Satoshi; Kanda, Nobuyuki; Itoh, Yousuke; Mori, Masaki
Abstract: WIMPs are promising dark matter candidates. When WIMPs collide with a mirror equipped with interferometric gravitational wave detectors, we expect that characteristic motions of the pendulum and mirror are excited, and those signals could be extracted by highly sophisticated sensors developed for gravitational wave detection. We analyze the motions of the pendulum and mirror, and estimate the detectability of these motions. For the "Thin-ET" detector, the signal to noise ratio may be 1.7 ( m DM 100 GeV ), where m DM is the mass of a WIMP. We may set a more strict upper limit on the cross section between a WIMP and a nucleon than the limits obtained by other experiments so far when m DM is approximately lower than 0.2 GeV. We find an order of magnitude improvement in the upper limit around m DM = 0.2 GeV.